السمات القيادية ودورها في نجاح الداعية الأردني –دراسة تحليلية - سناء زهير عبد الوالي الرفوع
This study dealt with leadership traits and their role in the success of the Jordanian preacher in the light of the story of Dhul-Qarnayn. The study aimed to explore the personal leadership traits of the Jordanian preachers in the light of the story of Dhul- Qarnayn. Inferring the intellectual leadership traits of the Jordanian preachers in the light of the story of Dhul-Qarnayn; identifying the social leadership characteristics of the Jordanian preachers in the light of the story of Dhul-Qarnayn; concluding the relationship between leadership traits and the success of Jordanian preachers. To achieve these goals, the quantitative method was applied through the descriptive analytical approach. The study population consisted of all imams accredited by the Jordanian Ministry of Awqaf, Islamic Affairs and Holy Sites, and affiliated to the Amman First Awqaf, and they numbered 224 imams. The first Amman Endowment Directorate has been approved because it represents the largest size among the Kingdom's directorates and has the largest share in the target group of society. The random sample was applied to 30% of the study population. Data were analyzed using the SPSS package. The study reached several results, including that the personal, intellectual and social leadership traits are available to the Jordanian preachers; There is a relationship between leadership traits and the success of Jordanian preachers. There is also a significant relationship between these characteristics and the success of preachers in achieving their goals. Among the recommendations proposed by the study is the need to take advantage of the leadership characteristics of Jordanian preachers and apply them in the advocacy curriculum and other relevant institutions, by training preachers to learn, understand and apply these characteristics; And the work of a comprehensive strategic plan to raise a generation of preaching leaders, on sound scientific and religious foundations to achieve the goals in the light of sound Islamic law.